2021
DOI: 10.1088/2053-1583/ac08f2
|View full text |Cite
|
Sign up to set email alerts
|

Strain engineering 2D MoS2 with thin film stress capping layers

Abstract: In this work, we induce on-chip static strain into the transition metal dichalcogenide (TMDC) MoS2 with e-beam evaporated stressed thin film multilayers. These thin film stressors are analogous to SiNx based stressors utilized in CMOS technology. We choose optically transparent thin film stressors to allow us to probe the strain transferred into the MoS2 with Raman spectroscopy. We combine thickness dependent analyses from Raman peak shifts in MoS2 and atomistic simulations to understand the strain transferred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 62 publications
5
30
0
Order By: Relevance
“…In Figure 6 e, due to compression, we observed a blueshift in ω G and redshift for tensile strain in Figure 6 f (see SI Section VI ). On comparing our results for 6° and 13.2° systems with the experimental data reported by Peña et al 73 and Gao et al, 7 respectively, we found good agreement between them (magenta data points in Figure 6 e,f). Finally, to achieve an experimental validation of our stacking identification method as well as to highlight that the global behavior, such as Raman scattering, is tied to local structural configurations, we used our calculated AF s of reconstructed TBGs in BOLS to predict the Raman G-band frequencies of heterostrained systems (see SI Section I for details).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In Figure 6 e, due to compression, we observed a blueshift in ω G and redshift for tensile strain in Figure 6 f (see SI Section VI ). On comparing our results for 6° and 13.2° systems with the experimental data reported by Peña et al 73 and Gao et al, 7 respectively, we found good agreement between them (magenta data points in Figure 6 e,f). Finally, to achieve an experimental validation of our stacking identification method as well as to highlight that the global behavior, such as Raman scattering, is tied to local structural configurations, we used our calculated AF s of reconstructed TBGs in BOLS to predict the Raman G-band frequencies of heterostrained systems (see SI Section I for details).…”
Section: Resultssupporting
confidence: 88%
“…Heterostrain-assisted peak splitting of the top and bottom layers (as shown in the schematic) is also denoted. Parts (e) and (f) also show the close alignment of bond order length strength (BOLS)-estimated data using reconstructed AF s ( AF recons ) with DFT-calculated and experimental data (reported by Peña et al 73 and Gao et al 7 ) as compared to that using rigid TBG AF s ( AF rigid ). The error bars shown for experimental data are inserted directly from the cited articles.…”
Section: Resultssupporting
confidence: 64%
“… 4 One benefit of the Sternheimer technique is the ability to avoid computing the (many) empty states by introducing the projector to the empty states. 70 As a result, less time is spent idle on the CPU and RAM. The calculation will consume much CPU time across a wide frequency range.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although many theoretical works predicted that biaxial strain can tune more effectively the band structure of MoS2 [16][17][18]24,25,29,30,34,44], most of the experimental works only deal with the specific case of uniaxial strain [19,20,22,[26][27][28]33,35,[37][38][39][40][41][45][46][47]49,50]. To date, only a handful of experimental works explored the application of biaxial strain to atomically thin MoS2 using piezoelectric substrates [21], thermal expansion mismatch [31,36,42,43,51], exploiting the presence of naturally occurring bubbles [48,52,53], the creation of artificial blisters [32,54,55] or bubbles [56][57][58], a thin film stressor method [59] or a capillary-pressure-induced nanoindentation method [60]. All these methods present some disadvantages (complexity, cross-talk, etc.)…”
mentioning
confidence: 99%